Prepartum Fibrinogen Levels Can Predict Excessive Hemorrhage After Vaginal Delivery - Kender Ertürk, Nergis; Taşgöz, Fatma Nurgül; Yenigül, Nefise Nazlı; Yaşa, Fatma Nur; Kırşan İleri, Emine; Ertürk, Anıl (Cerrahpaşa Medical Journal, 2022)
Objective: The aim of this study is to investigate the relationship between maternal prepartum fibrinogen level and other coagulation tests and blood loss in the third stage of labor. Methods: This prospective clinical study was performed in a tertiary center between September 2021 and March 2022. A total of 1217 singleton pregnancies between 37 and 42 weeks hospitalized for vaginal delivery were included in the study. Maternal predelivery blood samples were taken for complete blood count and biochemical and coagulation tests. Demographic, clinical, and follow-up data of the patients were recorded. Blood loss in the third stage of labor was measured quantitatively with transparent collecting bags. Patients were divided into 2 groups as blood loss < 500 mL and blood loss ≥ 500 mL and then compared among variables. Factors predicting excessive bleeding were defined by regression analysis. Receiver operating characteristic analysis was performed for fibrinogen to predict hemorrhage. Results: Of the 352 patients, 296 (84.1%) had blood loss < 500 mL and 56 (15.9%) had blood loss ≥ 500 mL. The demographic and clinical features of the groups were similar. The prepartum fibrinogen value was significantly lower in the blood loss ≥ 500 mL group (447.48 ± 79.40 mg/dL vs 486.67 ± 104.77 mg/dL, P = .008). There was a significant negative correlation between the blood loss volume and prepartum fibrinogen (R2 = −0.123, P = .021). The odds ratio of fibrinogen level to predict hemorrhage was 0.99 with 95% CI (β = −0.004, odds ratio = 0.996 (0.993-0.999), P = .010). The cut-off level of fibrinogen to predict blood loss ≥ 500 mL was 452 mg/dL with a sensitivity of 66.1% and a specificity of 57.1%. Conclusion: Prepartum fibrinogen level could be an indicator to detect postpartum hemorrhage in risk-free population. Cite this article as: Kender Ertürk N, Taşgöz FN, Yenigül NN, Yaşa FN, Kırşan İleri E, Ertürk A. Prepartum fibrinogen levels can predict excessive hemorrhage after vaginal delivery. Cerrahpaşa Med J. 2023;47(1):60-63.